Effects of seed size and nursery media on the germination and seedling growth of Plukenetia conophora - Onwubiko, Nwakuche Chinenye; Enwereji, Raymond Onyedikachi (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
Research on the effects of seed size, soil-based and soilless media to determine the best condition for increased seedling production of African walnut was carried out at the green house of Department of Crop Science and Technology, Federal University of Technology, Owerri. Seed size was categorized into 10.23 to 10.31g (for large seeds) and below 10.23g (for small seeds). Soil-based nursery medium was sawdust mixed with topsoil volume by volume (v/v) 1:1, while soilless was sawdust alone. The experiment was a 2×3 factorial in a complete randomized design with 6 replications. Data were collected on number of days to emergence, plant height at 4, 8, and 12 weeks after planting (WAP), and number of leaves at 4, 8, and 12 WAP. Data collected were tested with analysis of variance (ANOVA), and treatment means were separated with Fishers least significant difference at 5% level of probability. Result showed that large seeds planted on soil-based media performed best in all the assessed traits. The inference is that high quality seedlings of African walnut can be produced by planting large seeds in soil-based media.